2017
DOI: 10.3390/s17061411
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Disciplinary Approach to Remote Sensing through Low-Cost UAVs

Abstract: The use of Unmanned Aerial Vehicles (UAVs) based on remote sensing has generated low cost monitoring, since the data can be acquired quickly and easily. This paper reports the experience related to agave crop analysis with a low cost UAV. The data were processed by traditional photogrammetric flow and data extraction techniques were applied to extract new layers and separate the agave plants from weeds and other elements of the environment. Our proposal combines elements of photogrammetry, computer vision, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…The research by Calvario et alRemote Sens. 2019, 11, 1023 3 of 24 on agave control is a good example of the ability of UAV mixing computer vision and data mining technique in precision agriculture [26].Another example is the LABFVC algorithm proposed by Liu [19]. Passing by the L*a*b* color space, the Fractional Vegetation Cover (FVC) is extracted automatically.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The research by Calvario et alRemote Sens. 2019, 11, 1023 3 of 24 on agave control is a good example of the ability of UAV mixing computer vision and data mining technique in precision agriculture [26].Another example is the LABFVC algorithm proposed by Liu [19]. Passing by the L*a*b* color space, the Fractional Vegetation Cover (FVC) is extracted automatically.…”
mentioning
confidence: 99%
“…Remote Sens. 2019, 11, 1023 3 of 24 on agave control is a good example of the ability of UAV mixing computer vision and data mining technique in precision agriculture [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of UAVs in agriculture [36][37][38]56,57,62], horticulture [51], plant ecology [66,68,89], and forestry [59,61,62,65] is increasing worldwide. However, UAVs were not heretofore used to quantify the flower production of black locust.…”
Section: Discussionmentioning
confidence: 99%
“…Data from UAV-borne sensors have been used to provide indirect estimates of biomass, grain yield [22], and nitrogen status [23], and the output of multi-spectral sensors can produce an array of vegetation indices, including the normalized difference of the vegetation index (NDVI) [24]. UAVs are employed to detect and monitor pest infestations [25,26], analyze the structure of vegetation [27], detect nutrient deficiencies, and monitor weed and flower density in crop fields [28][29][30]. Müllerová et al [31] recently demonstrated that UAV imagery could be used to successfully differentiate between flowers of different invasive species.…”
mentioning
confidence: 99%